Arundinosides I-IX and graminifolosides A-B: 2R-benzylmalate and 2R-isobutylmalates derivatives from Arundina graminifolia (D.Don) Hochr. with antioxidant, cytocompatibility and cytoprotective properties. (February 2023) - Auberon, Florence; Olatunji, Opeyemi Joshua; Waffo-Teguo, Pierre; Olatunde, Oladipupo Odunayo; Singh, Sudarshan; Bonté, Frédéric; Mérillon, Jean-Michel; Lobstein, Annelise
Abstract: Phytochemical investigation of the underground parts of Arundina graminifolia D.Don Hochr was conducted leading to the isolation of nine new glucosyloxybenzyl 2 R -benzylmalate and two new glucosyloxybenzyl 2 R -isobutylmalate derivatives. The compounds were purified using chromatographic techniques and their structures were deduced based on spectroscopic techniques including nuclear magnetic resonance and high-resolution mass spectrometry as well as comparing with previous literature. The antioxidant activities of the isolated compounds were also evaluated. The compounds showed potent antioxidant activities in the ABTS radical scavenging, DPPH radical scavenging and FRAP activities. Furthermore, the isolated compounds were observed to exert minimal cytotoxic effects against RAW 264.7 cell, suggesting biocompatibility as well as cytoprotective effects against hydrogen peroxide induced cell toxicity. Graphical abstract: Image 1 Highlights: Eleven new glucosyloxylbenzyl 2R-malates derivatives were isolated from Arundina graminifolia D.Don Hochr. The structures were established based on spectroscopic data analyses. Six compounds showed potent ABTS radical scavenging, DPPH radical scavenging and FRAP activities. The compounds exerted minimal cytotoxic effects against RAW 264.7 cell and showed cytoprotective effects against H2O2 induced cell death.